2016
DOI: 10.5354/0719-0581.2015.38402
|View full text |Cite
|
Sign up to set email alerts
|

Autoritarismo y conciencia de muerte en estudiantes universitarios españoles

Abstract: Resumen: El objetivo del presente estudio fue relacionar el autoritarismo y la conciencia de muerte, postulándose que los sujetos con un mayor grado de autoritarismo presentarían más miedo ante la muerte propia y ajena. Mediante un muestreo bietápico de conveniencia con submuestreo aleatorio intragrupo se seleccionaron 202 estudiantes universitarios españoles con edades entre los 18 y los 25 años (M = 20,50; DT = 2,57). Los resultados aportan evidencias empíricas acerca de las diferencias significativas en fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
1
Order By: Relevance
“…In view of this, it was possible to identify that 12.75% of the total sample were in the preconventional stage, this being the level with the lowest frequency among the study sample. This result differs from that found by Juarez and Tananta (2020) because they found that most of the university students in their sample were at the preconventional level of moral judgment (58.75%), so it was determined that the determining moral judgment among the students was preconventional. It should be noted that at this level the moral sense and judgment is assumed in such a way that the norms are accepted and if they favor one’s own interests.…”
Section: Discussioncontrasting
confidence: 80%
“…In view of this, it was possible to identify that 12.75% of the total sample were in the preconventional stage, this being the level with the lowest frequency among the study sample. This result differs from that found by Juarez and Tananta (2020) because they found that most of the university students in their sample were at the preconventional level of moral judgment (58.75%), so it was determined that the determining moral judgment among the students was preconventional. It should be noted that at this level the moral sense and judgment is assumed in such a way that the norms are accepted and if they favor one’s own interests.…”
Section: Discussioncontrasting
confidence: 80%